Harnessing the Medicinal Potential of SwertiaChirata: A Phytochemical Strategy for Controlling Coronavirus Symptoms Like High Fever and Anxiety - Dilip Thakur (International Journal of Biomedical Innovations and Engineering, 2023)
The current investigation focuses on exploring the therapeutic capacities of SwertiaChirata, colloquially known as Chirata, in managing the symptomatic displays of coronavirus infections. Chirata, a member of the Gentianaceae family, is a distinguished herb extensively used in Ayurvedic and Unani medicinal traditions, acknowledged for its myriad of healing qualities. In addition to its regular use in combating fever and loss of appetite, its prominent antioxidant traits position it as an integral part of various health-boosting tonics. Considering the symptomological parallelism between the effects of Chirata and the erratic feverish symptoms often detected in coronavirus patients, our study emphasizes the potentiality of the herb in handling these signs. This could offer a viable substitute, subsequently lowering the reliance on medications like paracetamol, typically linked to unfavorable outcomes. SwertiaChirata is home to a wide variety of biologically active substances like Xanthones, flavonoids, iridoids, glycosides, and triterpenoids. These components have exhibited significant biological activities, including antimicrobial, anti-inflammatory, anticarcinogenic, antioxidant, and hypoglycemic properties. The therapeutic power of these secondary metabolites offers hopeful routes for managing coronavirus symptoms. The broad medicinal applications of Chirata, ranging from treating liver disorders, chronic fevers, and anemia in Ayurveda to serving as a tonic and antiinflammatory agent in Unani medicine, validate the herb's therapeutic flexibility. The presence of unique biologically active substances and a variety of minerals contribute to this wide array of healing properties. Moreover, Chirata has proven successful against both Gram-positive and Gram-negative bacteria, amplifying its significance in the modern healthcare scenario. The Quantitative Structure- Activity Relationship (QSAR) study related to immunity boosting is yet to be comprehensively studied, especially in regards to preventing coronavirus-like diseases. However, the identified traits of Chirata's biologically active substances offer promising initial steps towards effective symptom management strategies. This investigation underscores the critical need to incorporate such powerful herbal remedies into conventional allopathic medicine, proposing a sustainable, efficacious strategy to strengthen our fight against the daunting threats presented by pandemics such as coronavirus.
Keywords: Chirata; Coronavirus; Herbal Extract; Immunity Enhancement; Phytochemicals; SwertiaChirata; Symptom Management; Xanthones